2020
DOI: 10.1002/arch.21760
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expression of five genes in the mevalonate pathway of the Chinese white pine beetle, Dendroctonus armandi (Curculionidae: Scolytinae)

Abstract: The Chinese white pine beetle Dendroctonus armandi (Tsai and Li) is a significant pest of the Qinling and Bashan Mountains pine forests of China. The Chinese white pine beetle can overcome the defences of Chinese white pine Pinus armandi (Franch) through pheromone‐assisted aggregation that results in a mass attack of host trees. We isolated five full‐length complementary DNAs encoding mevalonate pathway‐related enzyme genes from the Chinese white pine beetle (D. armandi), which are acetoacetyl‐CoA thiolase (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Previous studies in plants showed that the expression levels of the key genes on terpenoid synthesis pathway, such as Hevea brasiliensis [45] and Picrorhiza kurroa [46], changed in the same trend. In recent studies, it was found that the expression levels of key enzymes in the terpenoid synthesis pathway of plants and animals such as Dendroctonus and armandi also changed in the same trend [47]. The analysis of protein-protein interaction with MDD in A. thaliana showed that there was interaction and coexpression relationship between the key enzymes in the terpenoid synthesis pathway, which may explain the above expression trend.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in plants showed that the expression levels of the key genes on terpenoid synthesis pathway, such as Hevea brasiliensis [45] and Picrorhiza kurroa [46], changed in the same trend. In recent studies, it was found that the expression levels of key enzymes in the terpenoid synthesis pathway of plants and animals such as Dendroctonus and armandi also changed in the same trend [47]. The analysis of protein-protein interaction with MDD in A. thaliana showed that there was interaction and coexpression relationship between the key enzymes in the terpenoid synthesis pathway, which may explain the above expression trend.…”
Section: Discussionmentioning
confidence: 95%
“…Isopentenyl diphosphate isomerase ( IPPI ) catalyzes the conversion of isopentenyl pyrophosphate (IPP) to dimethylallyl pyrophosphate (DMAPP); subsequently, IPP and DMAPP were condensed head-to-tail manner to produce geranyl diphosphate (GPP); this head-to-tail condensation can be repeated by the further reaction of GPP with IPP, yielding the JH precursor farnesyl diphosphate (FPP) [ 11 ]. The expressions of eight enzymes of the mevalonate pathway have been previously examined in Dendroctonus armandi [ 12 , 13 ]. During the late steps proceeding from farnesyl diphosphate to JH, FPP is transformed sequentially to farnesol, farnesal, farnesoic acid, methyl farneosate and JH [ 10 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sulcatone is a possible intermediate, which may be derived from the dioxygenase activity on GGPP (Blomquist et al, 2010; Keeling et al, 2013; Tittiger & Blomquist, 2017). In D. armandi, AACT , HMGS , HMGR , MK , PMK , MPDC , G/FPPS , and geranylgeranyl pyrophosphate synthase ( GGPPS ) have been cloned in full length, and the gene accession numbers are shown in Table (Sun et al, 2020; Wang et al, 2020; Yu et al, 2015). Yu et al (2015) and Wang et al (2020) showed that both injected JHIII and feed could increase the expression levels of HMGS , HMGR , G/FPPS , and IDI messenger RNA in both males and females, and cause high transcript levels mostly in the midgut tissue of D. armandi .…”
Section: Introductionmentioning
confidence: 99%